Mental health literacy among adolescents: Evidence from a community-based study in Delhi. (June 2022) - Ahmad, Aftab; Salve, Harshal Ramesh; Nongkynrih, Baridalyne; Sagar, Rajesh; Krishnan, Anand
Background: Mental Health Literacy (MHL) is the ability to recognize mental disorders, along with knowledge of professional help available, effective self-help strategies, skills to give support to others, and knowledge of how to prevent mental disorders. Adequate MHL is linked to better health-seeking behavior and management of mental illness. Aim: To assess the MHL related to depression and anxiety among adolescents of age 15 to 19 years residing in Delhi Methods: A survey was conducted among adolescents in southeast Delhi. MHL was assessed using sex-matched vignettes of Common Mental Disorders (CMDs) like depression and anxiety. MHL was assessed under domains of identifications of disorders, help-seeking behavior, knowledge about prevention, and stigmatizing attitude toward the respective illness. Statistical analysis was done in STATA and percentage of participants with adequate MHL in various domains was calculated, and difference between various groups was examined using chi-square test. Results: A total of 491 adolescents participated (response rate of 87.2%) of whom a 50.3% were girls and 57.8% were 15 to 17 years of age. Only 50 (10.2%) participants identified depression vignette as that of depression and 51 (10.4%) identified vignette of anxiety disorder as the same. No statistically significant gender differential in MHL was seen ( p value = .8). The stigmatizing attitude, assessed by asking a series of questions suggesting stigma toward the particular illness, was observed among almost all participants (depression -99.4%, and anxiety disorders -96.1%). 18.3% and 18.7% of participants reported correct knowledge about the prevention of depression and anxiety respectively. Four hundred and twenty-two (86%) identified the need to seek help for symptoms reported in vignettes. Of these, 234 (55%) preferred parents, and 62 (14.7%) look after friends for any help. Conclusion: Adolescents residing in Delhi reported poor MHL for Common Mental Disorders. High stigma and poor help-seeking behavior was also observed among the participants toward CMDs